Characteristics of Water Storage Capacity and Water Storage Efficiency of ‘Biotextile’ Growing Medium for Erosion Resistance - Utami, Dyah Nursita; Kusumastuti, Etty; Sudiana, Nana; Rahayu, Budi; Hidayat, Nur; Sulistiawan, Insan Nur; Purnomo, Agus; Atang; Sittadewi, Euthalia Hanggari (Berkala Ilmiah Biologi, 2023)
Abstract: Biotextile is an innovation in erosion-resistant growing media technology, made from organic cocopeat supplemented with Legume Cover Crop (LCC) seeds and coated with biofertilizer. In its application, the success of biotextiles is determined, among other things, by the capacity and efficiency of water storage in the media The capacity and water storage efficiency of biotextile media will determine the success of growth in field applications. From field tests conducted on the sloping land of the Ciater reservoir cliffs, South Tangerang, it was shown that on the 4th day the LCC seeds had started to grow, on the 10th day they had grown in all biotextile cells, and at the age of 3 months the LCC plant canopy had covered almost all of the soil surface at the test field. Based on the growth test results, biotextile characterization tests have been carried out, which include measuring water content (KA), water storage capacity (KPA), and water storage efficiency (Es). Based on these test results, a biotextile characteristic test has been carried out which includes water content (KA), water storage capacity (KPA), and water storage efficiency (Es) to find out the characteristics of KPA and Es in evaluating its success and to prove the hypothesis that KPA and biotextile Es support the successful growth of land cover plants (LCC). The measurement of KA biotextile was carried out using the gravimetric method, while KPA and Es were measured using the immersion method, which was carried out in the Serpong laboratory. From the results of laboratory analysis, KA reached a range of values: 40–80%, KPA = 74.41–297.59%, and Es = 21%–75.5%. Apart from the results of plant growth and laboratory results, from a physical perspective, the performance of biotextiles can be seen in reducing the energy of rainwater blows, reducing the flow rate of surface water, and reducing soil erosion.